High carbohydrate as obese diet is not yet available commercially for monkeys. Therefore, this preliminary study was to carry out nutrient intake and digestibility of cynomolgus monkeys (Macaca fascicularis) fed with high soluble carbohydrate diet compared to monkey chow. Five adult female macaques (average body weight 2.67 kg) were made to consume freshly diet. Commercial monkey chows (contains 3500 cal/g energy and 35% starch) were fed to three adult females (average body weight 3.62 kg). Nut - DEWI APRI ASTUTI; IRMA HERAWATI SUPARTO; DONDIN SAJUTHI; I NENGAH BUDIARSA (HAYATI Journal of Biosciences, 2009)
High carbohydrate as obese diet is not yet available commercially for monkeys. Therefore, this preliminary study was to carry out nutrient intake and digestibility of cynomolgus monkeys (Macaca fascicularis) fed with high soluble carbohydrate diet compared to monkey chow. Five adult female macaques (average body weight 2.67 kg) were made to consume freshly  diet. Commercial monkey chows (contains 3500 cal/g energy and 35% starch) were fed to three adult females (average body weight 3.62 kg). Nutrient intakes and digestibility parameters were measured using modified metabolic cages. Result showed that  average of protein, fat, starch, and energy intakes in treatment diet were higher than control diet (T-test). Fat intake in the treatment diet was three times higher, while starch and energy intakes were almost two times higher than monkey chow. Digestibility percentage of all nutrients were the same in both diets except for the protein. The study concludes that the freshly prepared high sugar diet was palatable and digestible for the cynomolgus monkeys. Further studies are in progress to develop obese diet high in energy content based on fat and source of starch treatments.         Key words: Macaca fascicularis, obese, metabolic cages, intake, digestibility